MyRecipe - Diana, khateeb; Enas, Adwan (My University, 2017)
We choose to design a program that helps in the side of the cooking and cares about several other things like Fitness and Health that's because this idea has become highly desirable for everyone, whether women or even men. The program will be designed as mobile application so it will be easily accessible to users. This project should be able to brings recipes from all of the world to your mobile device ,spreads your recipes all over the world ,you can easily finding recipe by searching it and easily prepare it by looking at its ingredients , directions and time , you can also use recipe timer which will notify you after a specific cooking time, you can also add any recipe you like and add photo and video with it every added recipe has automatic calories and vitamins calculation ,you can also search a recipe by name ,chief name ,calories ,ingredients its contain ,and time. you can share ,rate ,or even add this recipe to your favorite list and comment to it, each chief has its own profile page to contact with him through his phone ,email, website ,finally you can keep track with your diet by entering your height and your weight and add your daily meals with automatic calories calculate for them and compare them with your daily calories needed, all of this to keep you healthy and fit all of the time. We use for this application JAVA,XML,PHP languages, and it is compatible with Android The API will be written in java using Android studio , for the Database use XAMPP server.